Deficientes visuais e prática de atletismo paralímpico: uma análise bioecológica desta relação - LOPES, Alexsandro dos Santos (2023)
This research is focused on resilience in the development of visually impairment people, from a contextual approach with the bioecological theory of Urie Bronfenbrenner (1996). The public participating in this study is composed of adolescents with visual impairment, aged between 12 and 18 years old, who practice Paralympic athletics. The data collection was done through a semi-structured questionnaire with 10 (ten) questions related to some systems presented by Bronfenbrenner (1996): microsystem, mesosystem and chronosystem. Based on this, we understand the notion of resilience from Placco (2002), verifying and understanding their role in the way Paralympic athletes face adversities and how they manage to overcome these difficulties. The data indicate that Paralympic athletics allows the insertion of the athlete to different contexts that provide situations in which the individual assumes a resilient position, contributing to physical, social and psychological development.